The Role of Professional Competence in Improving the Quality of Madrasah Ibtidaiyah Teacher Education - El-Masri, Omar; Tanaka, Hiroshi (ELEMENTARY : Journal of Primary Education, 2024)
Improving the quality of education in Madrasah Ibtidaiyah depends heavily on the professional competence of teachers who teach at this level. This article aims to examine the role of teachers' professional competencies in improving the quality of education in Madrasah Ibtidaiyah through a comprehensive literature review. The research analyzes various aspects of professional competence, including pedagogical understanding, mastery of materials, classroom management skills and adaptability to curriculum changes and educational technology. The results showed that strong professional competencies contribute significantly to the effectiveness of teaching and learning and create a conducive learning environment for students. In addition, it was found that continuous training and development programs are essential in strengthening teachers' competencies, which in turn improves the quality of education in Madrasah Ibtidaiyah. This article recommends increased support for teachers' professional competence development as a key strategy to achieve higher education standards in madrasahs.